TINJAUAN YURIDIS TENTANG PIDANA MATI TERHADAP PELAKU TINDAK PIDANA KORUPSI BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2001PERUBAHAN ATAS UNDANGUNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Lili Wulansari; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Death penalty is an exception criminal in the form of elimination of lifeand can be threatenesd for criminal acts that endanger safety, cracking, statesecurity, blocking the nets of the revolution, anti-revolutionary (subversion) andcan disrupt the country's economy which aims to establish and build a just andprosperous society .The purpose of this study is to find out about the imposition of capitalpunishment on the perpetrators of corruption, capital punishment currently asoutlined in Law Number 20 Year 2001, the amendment to Law Number 31 of 1999is not very good, in Article 2 Paragraph ( 2) as well as the explanation in Article2 Paragraph (2) there is the term "certain conditions", with the existence of saidparticular circumstances which has resulted in the difficulty of imposing capitalpunishment on the perpetrators of corruption, so far there has never been oneperpetrator of corruption capital punishment even though there are laws thatregulate it.The use and imposition of capital punishment should be more effective andintensified through the formulation of regulations regarding capital punishmentfor perpetrators of corruption. Because if we see the existence of capitalpunishment in tackling criminal acts of corruption in Indonesia, it does notsupport the government program, which is a government that is free fromcorruption, because it has been implemented since the death penalty forperpetrators of corruption that in Law No. 31 of 1999 Jo Law Number 20 Year2001, until now there are no perpetrators of criminal acts of corruption sentencedto death. And even capital punishment which is formulated as an effort to reduce(scare) perpetrators of corruption in Indonesia is not functioning, on the contrarycriminal acts of corruption in Indonesia are increasingly thriving in Indonesia.Keywords: Review of Juridical - Criminal Health - Corruption Crime